Evolution of conventional to diversified livestock production systems in the Mexican tropics - Herrán-Aguirre, Mariana; Guevara-Hernández, Francisco; La O-Arias, Manuel; Mandujano-Camacho, Hernán; Nahed-Toral, José; Aguilar-Jiménez, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Cattle ranches in Mexico have demonstrated a remarkable ability to adapt to changing economic, environmental, and social conditions. In a context where traditional cattle ranches were being replaced by conventional technologies, diversification has become a fundamental strategy to ensure their sustainability and resilience. The term “ranch” used to encompass various agribusiness units with different forms of ownership and management. However, today, a conventional cattle ranch is characterized by its focus on the core activity of grazing. The central objective of the article was to analyze the evolution of cattle ranches in Mexico, focusing on how diversification became a fundamental strategy to address challenges over time and adapt to changing economic, environmental, and social conditions. To achieve this, a bibliographic search and comprehensive analysis of the state of the art related to the organizational structure of cattle ranches were conducted. This process provided the necessary theoretical foundations for the conceptualization of cattle ranches based on their structure, diversity of functions, products, and activities. Ultimately, it was concluded that the evolution of cattle ranches in Mexico reflected their continuous adaptation to changing economic, environmental, and social conditions, with diversification being a key strategy to ensure the sustainability and resilience of livestock farms.